Interface entre EJA e educação especial: potencialidades da diferenciação pedagógica - Bueno, Melina Brandt (Universidade Federal de São Carlos, 2024)
Given the complexity and diversity of Adult Education (EJA), it is essential to adopt teaching strategies that consider the different educational needs and contribute to the development and autonomy of individuals. The study begins by questioning the pedagogical practices developed, considering differentiated instruction as a proposal to meet students' diversity. Thus, its general objective is to analyze perspectives and practices on differentiated instruction, according to teachers working in Adult Education. The specific objectives are to identify the levels of importance and difficulty of a set of differentiated instruction practices by teachers; analyze pedagogical practices and their interface with components of differentiated instruction; and understand the meaning of the reflective formative process focusing on the differentiated instruction approach and its implications in teaching practice. For this purpose, descriptive research was conducted, organized into two stages: the first based on survey research, with the application of a virtual questionnaire involving 115 teachers, followed by descriptive statistical analysis of the data; and the second, based on collaborative research, with data collection in virtual settings through reflective sessions, including study and reflection cycles, with four participants, followed by content analysis with thematic categorization. As results, the first stage identified the importance of differentiated instruction practices and low difficulty in their implementation; with the development of the reflective formative process, the potential application of differentiated instruction practices in the context of Adult Education was verified, with some particularities of this modality highlighted, which could become obstacles if not considered in teacher planning and school organization. Additionally, there was an alignment between the studied practices and those already conducted by the participants. The study also indicated a positive evaluation of collaborative development and signs of changes in teaching practice, emphasizing the need for ongoing training programs for teachers addressing the specific context of Adult Education, as well as considering their experiences.
Interface between Adult Education (EJA) and special education: potential of differentiated instruction
Keywords: Educação especial; Educação de jovens e adultos; Prática pedagógica; Formação docente; Special education; Adult education; Pedagogical practice; Teacher training; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO